PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU PROSOSIAL PESERTA DIDIK KELAS TINGGI DI YPS MI MANGGARUPI KABUPATEN GOWA - Widiastuti Widiastuti; Muhammad Yahdi; Ulfiani Rahman; Suarti Suarti (JIPMI (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah), 2022)
This study discusses the effect of parenting on the prosocial behavior of high-class students at YPS MIManggarupi, Gowa Regency. This study aims to determine the parenting patterns of high-class studentsat YPS MI Manggarupi, Gowa Regency, to determine the prosocial behavior of students in high-classstudents at YPS MI Manggarupi, Gowa Regency and to determine the effect of parenting on students'prosocial behavior. high class at YPS MI Manggarupi, Gowa Regency. This research is a quantitativeresearch, using the 'ex post facto' method. The research subjects were high-class students at YPS MIManggarupi, Gowa Regency with a total of 77 of 154 students who were taken using the SimpleRandom Sampling technique. Data collection techniques were carried out through closed questionnairesand documentation. Data analysis used descriptive quantitative analysis and inferential analysis. Basedon the results of the analysis, it was found that the parenting pattern of high-class students YPS MIManggarupi Sungguminasa, Gowa Regency was in the very good category, namely 62.34%, theprosocial behavior of high-class students YPS MI Manggarupi Sungguminasa, Gowa Regency was inthe very good category, namely 70, 13%, and there is a significant effect of parenting on prosocialbehavior. This can be proven by the t-test which gets tcount of 15.942 where ttable is 0.2242 and b1coefficient is 0.012 with a probability of 0.020 <0.05. Meanwhile, the effective contribution of parentingstyle to prosocial behavior is 77.2%.